2023
DOI: 10.1101/2023.02.10.527988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple hosts, multiple impacts: the role of vertebrate host diversity in shaping mosquito life history and pathogen transmission

Abstract: The transmission of malaria parasites from mosquito to human is largely determined by the dietary specialization of Anopheles mosquitoes to feed on humans. Few studies have explored the impact of blood meal sources on the fitness of both the parasite and the mosquito. Our study investigated the effects of 3-4 consecutive blood meals from one of four vertebrate species (human, cattle, sheep, or chicken) on several fitness traits, including mosquito feeding rate, blood meal size, susceptibility to wild isolates … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…However, a recent study in Burkina Faso showed no fitness cost for feeding on alternative domestic hosts (cow and sheep), compared with humans, in An. coluzzii (Vantaux et al., 2023). Therefore, the strong association for feeding on humans should involve other biological determinants such as a greater sensitivity of anthropophilic mosquitoes to detect human skin volatiles.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study in Burkina Faso showed no fitness cost for feeding on alternative domestic hosts (cow and sheep), compared with humans, in An. coluzzii (Vantaux et al., 2023). Therefore, the strong association for feeding on humans should involve other biological determinants such as a greater sensitivity of anthropophilic mosquitoes to detect human skin volatiles.…”
Section: Discussionmentioning
confidence: 99%
“…Data and scripts for the theoretical modeling are available online: https://doi.org/10.5281/zenodo.7645483 (Vantaux, 2023b).…”
Section: Data Scripts Code and Supplementary Information Availabilitymentioning
confidence: 99%